To study dexmedetomidine’s effect on intraocular pressure after succinylcholine and endotracheal intubation - Surya Gowthami Katika,; Sri Harsha Merugu,; Jaya Chandra Tentu,; Rama Krishna Prasad Katuri, (Asian Journal of Medical Sciences, 2023)
Background: One of the most important preconditions for any anesthetic operation is perioperative hemodynamic stability during laryngoscopy and intubation, which has been the subject of extensive research and documentation. Numerous approaches have been proposed to protect the patient from the sympathetic reaction, intraocular pressure (IOP) response, and catecholamine response during laryngoscopy and intubation. Aims and Objectives: To study the efficacy of two doses of intravenous dexmedetomidine premedication given as a single bolus dose over 10 min, 0.4 μg/kg and 0.6 μg/kg, 10 min before induction in preventing the rise of intraocular pressure following succinylcholine administration and endotracheal intubation. Materials and Methods: A retrospective randomized study was conducted. Ethical committee permission and signed informed consent were obtained from 60 eligible patients before the trial began. Results: Premedication with either 0.4 mcg/kg I.V. or 0.6 mcg/kg I.V. of dexmedetomidine diluted in normal saline at a 2 mcg/mL concentration administered over 10 min before induction resulted in significant obtundation of the rise in IOP associated with succinylcholine administration and intubation. Sympathetic response to laryngoscopy and intubation was also significantly diminished. The dose of 0.4 mcg/kg I.V. produced the best hemodynamic stability. Conclusion: Therefore, from the above research it can be concluded that, before succinylcholine delivery and intubation, dexmedetomidine 0.4 mcg/kg I.V. can be used as a premedication in situations where an increase in IOP could be hazardous.